2015
DOI: 10.1016/j.ijhydene.2015.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precooled inlet gas temperature and mass flow rate on final state of charge during hydrogen vehicle refueling

Abstract: On-board compressed hydrogen storage Fast filling Refueling protocols Hydrogen precooling State of charge a b s t r a c t Short refueling time and high final state of charge are among the main hydrogen car user's requirements. To meet these requirements, without exceeding the tank materials safety limits, hydrogen precooling is needed. Filling experiments with different inlet gas temperatures and mass flow rates have been executed using two different types of on-board tanks (type 3 and 4). State of charge has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The experimental studies by Cebolla et al have also reported the cooling requirement for improvement of SOC of the tank. 46 The density obtained by filling of precooled H 2 is very near to target density of 40.2 kg/m 3 , and the SOC varies from 91% to 96%. However, the SOC could not be achieved the desired mark of 100%, but it is improved by an average of 2% to 3% at all filling rates for −40 and −20 C. The SOC obtained at a supply temperature of 0 C is close to the desired range for slow filling rates but decreases to less than 90% for higher filling rates.…”
Section: Simulation Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The experimental studies by Cebolla et al have also reported the cooling requirement for improvement of SOC of the tank. 46 The density obtained by filling of precooled H 2 is very near to target density of 40.2 kg/m 3 , and the SOC varies from 91% to 96%. However, the SOC could not be achieved the desired mark of 100%, but it is improved by an average of 2% to 3% at all filling rates for −40 and −20 C. The SOC obtained at a supply temperature of 0 C is close to the desired range for slow filling rates but decreases to less than 90% for higher filling rates.…”
Section: Simulation Resultsmentioning
confidence: 77%
“…However, dependency of SOC on supply temperature cannot be ignored because at higher supply temperature it goes below the desired mark of 90%. The experimental studies by Cebolla et al have also reported the cooling requirement for improvement of SOC of the tank …”
Section: Resultsmentioning
confidence: 99%
“…Both of them are set as the fitted parameters. Equation (13) is utilized to fit with the reference data [14], the results show a good agreement as shown in Figure 1, and the values of fitted parameters are listed in Table 1.…”
Section: Effect Of Inflow Temperature On Socmentioning
confidence: 68%
“…As stated above, the full-fill density of 70 MPa tank at 15 • C is 40.2 g/L, so the full-fill mass for these two tanks are 1.608 kg (Type III) and 1.1658 kg (Type IV), respectively. From [14], the initial pressure p 0 for the two tanks is set as 2 MPa, and both tanks are filled up to a final pressure p of 77-78 MPa, the ambient temperature T f is controlled at 291-300 K. Herein, the initial temperature T 0 inside tank is considered to be the same as the ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation